2022
DOI: 10.3389/fcvm.2022.970118
|View full text |Cite
|
Sign up to set email alerts
|

MitraClip for the treatment of heart failure with mitral regurgitation: A cost-effectiveness analysis in a Chinese setting

Abstract: BackgroundHeart failure (HF) with mitral regurgitation is associated with decreased survival. Guideline-directed medical therapy and transcatheter edge-to-edge repair (TEER) are the main options for HF patients with severe mitral regurgitation who are considered high-risk or prohibitive. To date, there have been no studies investigating the cost-effectiveness of MitraClip vs. optimal medical therapy (OMT) in a Chinese setting.MethodsA combined decision tree and Markov model were developed to compare the cost-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…8 Thus, there was a potentially large bias about the long-term cost-effectiveness evaluation in previous studies. [10][11][12][13] Although the use of MitraClip was associated with less HF re-hospitalization and death, which contributed to more QALYs gained and important cost savings during follow-up, our study showed that the cost-effectiveness of MitraClip was different across countries. The base-case analyses for three developed countries (the United Kingdom, Germany, and the United States) indicated that MitraClip + GDMT was cost-effective for HF patients with moderate-to-severe or severe secondary MR compared with GDMT alone, and both the one-way sensitivity analysis and the PSA showed that most results were robust.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…8 Thus, there was a potentially large bias about the long-term cost-effectiveness evaluation in previous studies. [10][11][12][13] Although the use of MitraClip was associated with less HF re-hospitalization and death, which contributed to more QALYs gained and important cost savings during follow-up, our study showed that the cost-effectiveness of MitraClip was different across countries. The base-case analyses for three developed countries (the United Kingdom, Germany, and the United States) indicated that MitraClip + GDMT was cost-effective for HF patients with moderate-to-severe or severe secondary MR compared with GDMT alone, and both the one-way sensitivity analysis and the PSA showed that most results were robust.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, our study is the first to evaluate the long-term cost-effectiveness of the MitraClip treatment based on the 5 year follow-up result of the COAPT trial. By using NYHA classes at a series of time points during a 5 year follow-up to calculate health utility instead of NYHA transition probabilities as reported in previous studies, [12][13][14][15] our study makes the estimation of health utility more precise because NYHA transition probabilities may not be uniformly distributed. A study reported by Baron et al estimated that the 5 year probability of all-cause death was 51.8% in the MitraClip group and 68.3% in the GDMT group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expenses within the decision tree and Markov model were combined to compute the overall cost, while the total effectiveness was determined using an analogous approach. The conversion of all costs to USD was based on the exchange rate of 6.4515 Chinese Yuan (CNY) to 1 USD [19]. Following the principles set forth by the China Guidelines for Pharmacoeconomic Evaluations, expenses occurring prior to 2021 and future costs were discounted at a rate of 0.05, with a variation between 0 and 0.08 [20].…”
Section: Plos Onementioning
confidence: 99%